Digital university: Approaches to the concept definition - G. A. Bannykh; S. N. Kostina (Obrazovanie i Nauka, 2022)
Introduction. The modern period of development of higher education is directly related to the ongoing digital transformation of public relations. The changes that occur in universities, in their external interactions and functions, basic principles and value-normative foundations, require methodological analysis and research.Aim. The aim of the research is to analyse the theoretical approaches to disclosing the concept and essence of digital universities.Methodology and research methods. The mix-method was used as a research design: qualitative analysis (studying the content of theoretical sources and context, analysing the content of a concept) and quantitative analysis (scientometric analysis of publications and keywords in databases).Results. The study showed that in the methodological terms, there is a problem of defining the concept of “digital university”: there are several theoretical approaches based on different understanding of the phenomenon and its role in the digital development of the university. The methodological problem is complicated by the urgent need to systematise the practical activities of modern universities, which classify themselves in one way or another in the “digital” format; therefore, this is much more difficult to do without a coordinated approach to the concept itself.Scientific novelty lies in an attempt to systematise theoretical approaches to defining the concept of “digital university” and the problem of the absence of a holistic interdisciplinary approach has been identified.Practical significance of the study is associated with the need to develop a regulatory model of a digital university based on a holistic concept for the subsequent analysis of the activities of universities. The results of the analysis can be used in scientific discussion to further define the concept of “digital university” and develop a general model of a digital university.